Food context and body mass index in adolescent - Oliveira, António (2020)
Background: In the last decades, the incidence of overweight and obesity has increased significantly worldwide, and Portugal wasn’t an exception. Nowadays the WHO places obesity among the ten major risk factors threatening health, considering the prevention of the obesity epidemic as a public health challenge priority in the twenty-first century. Objectives: Analyse the existence of causality of the food context variables (frequency of eating breakfast, number of daily meals, frequency of food intake between meals), as determining factors in the body mass index of adolescents. Methods: This study was observational and transversal, quantitative, non-experimental, descriptive and correlational, was conducted with 1467 adolescents with a mean age of 14.01, mostly female sex (52.3%), living in rural areas (63.32%) in various districts of Portugal mainland, attending between the 5th and 12th grade of public education, it is carried out an anthropometric assessment and stratification index of obesity based on the framework of the NCHS of CDC (2000). Results: Low daily breakfast intake has an effect with statistical significance which goes in the sense that the fewer times they ingest breakfast the higher becomes their BMI (χ2=12.273, p = .046). Intake of only three meals a day is associated with a higher body mass index (χ2 = 17.062, p= .009). Ingesting rarely or never food between meals has an effect with statistical significance, which shows that the lower intake between meals the higher the body mass index will be (χ2 = 19.451, p = .003). Conclusion: Inferences show that when monitoring the adolescent’s development its indispensible to value risk determinants, being crucial to combat and preventing these if chosen to implement intervention programs focused on the family.